Development of an automation and control design system for lowland tropical greenhouses - Wan Ismail, Wan Ishak; Razali, Mohd Hudzari; Tan, M. Y. (Universiti Putra Malaysia Press, 2013)
Vapour pressure deficit (VPD) analysis introduces an approach to develop a better basis for the control of the environment of lowland greenhouses in Malaysia. The study of vapour pressure deficit (VPD) is to show air moisture conditions for plant production while taking into account different temperature levels. The purpose of this project is to develop a real-time automatic temperature and relative humidity control system in the lowland tropical greenhouse using a PIC16f876A microcontroller. The controller will then be used to monitor the temperature, relative humidity and VPD in the planting of Chili Kulai (Titisan 15). The fertigation system was introduced to the greenhouse to fertilize and irrigate the plant as well as to provide moisture to the environment. A swamp cooler was used to bring down the temperature and increase moisture content in the greenhouse. Ventilators were installed to remove the heat in the greenhouse. The study was carried out in an experimental greenhouse located at the Institute of Advanced Technology, Universiti Putra Malaysia (UPM).